Innovation in MCAD education toward competency development using negative knowledge: From theoretical framework to practical implementation. Issue 3 (4th May 2018) - Mandorli, Ferruccio; Otto, Harald E.
ABSTRACT: With the rising importance of CAD models for product development and the recent strong promotion of hybrid geometric modeling from within the industry, the focus of teaching methods in current CAD education, as practiced in most institutions of higher education, needs to be reconsidered. From a pedagogical point of view, this situation represents a challenge, as it requires new, innovative teaching methodologies which advance the development of competency going beyond basic domain knowledge and skills limited to operating a CAD system. In this paper, a new and innovative direction for CAD education is offered, which is based on the integration of traditional teaching methods with an educational approach using negative knowledge. Central aspects of framework development and concept translation are presented together with promising results obtained through a multi-method oriented empirical study of this newly developed and now fully implemented approach. GRAPHICAL ABSTRACT: